2021
DOI: 10.1177/10464964211023558
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning Style Grouping Impact on Student Outcomes in Team Leadership Coursework

Abstract: This study explores how different team configurations based on members’ experiential learning styles impacted group level variables including team learning behavior, stages of team development, potency, psychological safety, and satisfaction in an undergraduate class. Groups with homogeneous learning styles experienced higher levels of friendship and lower levels of conflict, which were associated with greater satisfaction and more rapid progress through the stages of group development. Most significantly, sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Regarding teamwork and leadership skills in relation to teaching and learning styles, the present study does not show any potential in this area, as although group activities are conducted through STEM education, there is no evidence of the potential of teamwork and leadership skills in relation to teaching and learning styles. However, Orsini et al [56] showed that groups with homogeneous learning styles have lower levels of conflict and higher levels of friendship, associated with higher satisfaction, suggesting that students in social settings can progress at the same rate as the group develops [57].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding teamwork and leadership skills in relation to teaching and learning styles, the present study does not show any potential in this area, as although group activities are conducted through STEM education, there is no evidence of the potential of teamwork and leadership skills in relation to teaching and learning styles. However, Orsini et al [56] showed that groups with homogeneous learning styles have lower levels of conflict and higher levels of friendship, associated with higher satisfaction, suggesting that students in social settings can progress at the same rate as the group develops [57].…”
Section: Discussionmentioning
confidence: 99%
“…Learning styles, on the other hand, represent an important issue in learning in the twenty-first century, with students expected to participate actively in developing self-understanding and their environment engagement (El-Sabagh, 2021). Learning styles were used to identify students' characteristics to create homogenous and heterogeneous groups (Orsini et al, 2022). The presence of various learning styles is related to students' different abilities and individual preferences to learn (Baherimoghadam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%